A Systematic Literature Review of Quasi-Experimental Studies on Consumer Behavior in the Sustainability Domain - Mahajan, Yogesh; Kaul, Natashaa; Sharma, Sanjay (Indian Journal of Marketing, 2023)
Purpose : This study aimed to examine the literature on consumer behavior quasi-experiments in the sustainability domain and offer insights into how quasi-experiments are currently being used. Design/Methodology/Approach : After looking through 544 documents using a separate keyword search, a systematic quantitative review was done, and 159 pertinent papers were found from the Web of Science and Scopus databases up to 2021. The utilization of quasi-experiments in industrialized Western nations was the study’s main focus, followed by Asian nations, especially China and India. Few research used theoretical frameworks, and the quasi-experimental techniques used are restricted to treatment and control groups and the pre-post test approach. Findings : The majority of the research in this field, according to the study, has been conducted in developed Western nations, and the quasi-experimental techniques employed are restricted due to the employment of treatment and control groups and the pre-post-test procedure. The survey also discovered that a very small number of studies have used theoretical frameworks. Future research topics are suggested by the study, particularly the utilization of quasi-experiments with samples of women and LGBTI people. Practical Implications : Given that no studies in the literature have used this sample, the study offers useful guidance for conducting quasi-experiments with female and LGBTI subjects. The review sheds light on how consumer behaviour quasi-experiments are now being used in the sustainability field. Originality/Value : Given that it is the first review ever written on this subject, it is the first of its type. By offering insights into the current application of quasi-experiments in consumer behavior in the sustainability domain, the study adds to the body of literature and provides new avenues for investigation.